Development of a structured clinical operative test in assessing the competency of dental clinicians in exodontia - Bautista, Joy S.; Erlyn A. Sana, PhD (2010)
Exodontia is one of the most basic clinical procedures a dentist should be able to perform competently. In Philippine dental schools, assessment of this procedure is arbitrary, dependent on judgment of individual raters and not focused on its requisite skills. This is a descriptive study. Minimum competencies students should demonstrate while performing exodontia were generated from five content experts during a focus group discussion. The country's three largest and oldest dental schools based in Metro Manila were purposively chosen. All their 18 clinical instructors and 115/205 dental clinicians were surveyed regarding their perceptions on the current tool used for exodontias. Based on the standard competencies and gaps identified in the tool, a formative and summative assessment scheme in the form of a structured clinical operative test (SCOT) for exodontia was formulated. Subject experts reported that dental clinicians should be able to perform exodontia uneventfully. Students should demonstrate a comprehensive view of a given case in history taking, knowledge and skills in clinical examination, strong theoretical background on diagnosis of oral problems including their corresponding armamentaria and when exodontia is warranted, mastery of principles on anesthesia and their application to oral procedures and at least mechanism level of intra and postoperative management of exodontia. On the other hand, mean ratings of clinical instructors and dental clinicians showed that they were contented with the tools currently being used for exodontia but likewise concerned regarding their subjectivity, evaluator calibration, lack of immediate feedback, distribution of weights on each step, and too generalized criteria. The opinions of the subject experts and survey findings were used as basis in the development of the SCOT, both as a formative and summative evaluation scheme in determining the quality of dental clinicians' performance of exodontia. To prove its usefulness, the researcher recommends pilot testing of the SCOT.
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Maria Elizabeth M. Grageda PTRP MHPEd, Reader/Critic; Melflor A. Atienza MD MHPEd, Member; Nemuel S. Fajutagana MD MHPEd, Member; Marjorie C. Quieng DMD MS Dent Ed., Member.
Keywords: Tooth extraction; Exodontia